Leadership Abilities of a Military Manager, Professionalism of a Commander as the Guarantee of the Practice of Effective Activi-ty of a Military Organization - Bakhov, Ivan; Ryzhykov, Vadym; Kolisnyk, Oleh (International Journal of Engineering and Technology, 2018)
In their paper, the authors studied sequence of development and importance of leadership, military management as the basis of effective management of the military organization. The emphasis was placed on the managerial qualities of a modern military commander as a leader of a military organization. Leading talent for military commanders was announced on the example of Sun Tsu and Alexander Suvorov. It is stated that charismatic leadership as a special type of leadership is based neither merely on the law and the constitution as in legitimate leadership, nor on tradition as in traditional leadership, but solely on the special talent of a charismatic leader capable of enchanting and leading a mass of people. The authors suggested three groups of elements of the leader's image in relation to the political leader are outlined, namely, personal characteristics – physical, psycho-physiological features, his character, type of personality, individual style of decision making; social characteristics – the status of a leader associated with the official position, as well as related to the origin, wealth, etc. in the paper it is singled out the main psychological and pedagogical properties of the military commander and his functions in modern military management.